Pregnancy in end stage renal disease patients on dialysis - Naorungroj, Surarit; Sangthawan, Pornpen (Journal of the Nephrology Society of Thailand, 2022)
End stage renal disease (ESRD) among pregnant patients leads to various physiologic and gynecologic changes that rarely occur such as anovulatory menstruation and loss of libido. These changes can be less problematic or reversible after initiating renal replacement therapy especially kidney transplantation. Furthermore, these patients are usually comorbid with hypertension increasing the risk of progression to pre-eclampsia, affecting morbidity, mortality, and prognosis of both maternal and fetal outcomes. Appropriately adjusting the renal replacement therapy prescription to ensure adequate solute and fluid clearance as well as adequate control of blood pressure, could result in satisfactory maternal and fetal outcomes.